2000
DOI: 10.2337/diacare.23.6.796
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up in diabetic Charcot feet with spontaneous onset.

Abstract: A table elsewhere in this issue shows conventional and Système International (SI) units and conversion factors for many substances. Long-Term Follow-Up in Diabetic Charcot Feet With Spontaneous OnsetOBJECTIVE -To assess the long-term results after Charcot breakdown with spontaneous onset in diabetic feet.RESEARCH DESIGN AND METHODS -This study was retrospective. A total of 115 patients (140 feet), 107 with acute deformity and 8 with chronic Charcot deformity, were followed for a median of 48 months (range 6-11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
196
1
10

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(217 citation statements)
references
References 16 publications
10
196
1
10
Order By: Relevance
“…Other studies have similarly reported that a certain percentage of diabetic patients with Charcot arthropathy had a previous history of foot problems such as ulcer, surgery and/or amputation of the foot complex, along with a loss of protective sensation. (12,13,17) Foot ulcer in diabetic patients with loss of protective sensation commonly occurs at the plantar aspect because of the abnormal high plantar pressure. Delayed management and the absence of adequate pressure offloading of the foot ulcer may further delay wound healing, instigate infection and perpetuate the progression of foot deformity.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have similarly reported that a certain percentage of diabetic patients with Charcot arthropathy had a previous history of foot problems such as ulcer, surgery and/or amputation of the foot complex, along with a loss of protective sensation. (12,13,17) Foot ulcer in diabetic patients with loss of protective sensation commonly occurs at the plantar aspect because of the abnormal high plantar pressure. Delayed management and the absence of adequate pressure offloading of the foot ulcer may further delay wound healing, instigate infection and perpetuate the progression of foot deformity.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence and prevalence of CN varies between 0.1% to 0.4% of diabetic populations [24,25,26,27]. In one of the largest series published, 101 cases were found among 68000 consecutive diabetic patients between 1947 and 1970, giving an incidence of 1:680 [24].…”
Section: Epidemiologymentioning
confidence: 99%
“…Today, diabetes mellitus is the leading cause of a Charcot joint 13 . Though epidemiological data is weak, clinically overt Charcot joint is likely uncommon in large diabetes populations (incidence of 0.2 to 0.3%) 14,15 , but more frequent in populations of diabetic neuropathy reported from subspecialty clinics and radiologic surveys of patients with diabetic neuropathy [16][17][18] . In this patient, it is impossible to differentiate aspects of sensory and motor dysfunction into discrete phenomena caused by diabetic neuropathy versus CMT1A.…”
Section: Discussionmentioning
confidence: 99%